How Task Complexity Moderates the Relationship Between Well-being, Competency, and Auditor Performance? - Fransiscus Nicodemus Naiola; Donny Teguh Santoso Junias (Univiversitas Dr. Djar Wattiheluw, 2024)
This study analyzes the influence of Healthy Lifestyle, Psychological Well-Being, Self-Efficacy, Competency, and Experience on Auditor Performance, as well as the role of Task Complexity as a moderator. The study was conducted on auditors at the Regional Inspectorate of East Nusa Tenggara Province with 35 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed using Moderated Regression Analysis (MRA) with SPSS version 22. The results show that all independent variables have a significant positive effect on auditor performance. Task Complexity moderates the effect of Experience on Auditor Performance but does not moderate the influence of the other variables.